Vaterite vectors for the protection, storage and release of silver nanoparticles - Ferreira, Ana M.; Vikulina, Anna; Cave, Gareth W.V.; Loughlin, Michael; Puddu, Valeria; Volodkin, Dmitry (Journal of Colloid and Interface Science, 2023)
Silver nanoparticles (AgNPs) have found widespread commercial applications due to their unique physical and chemical properties. However, their relatively poor stability remains a main problem. An ideal way to improve the stability of AgNPs is not only to endow colloidal stability to individual nanoparticles but also to protect them from environmental factors that induce their agglomeration, like variation of ionic strength and pH, presence of macromolecules, etc. Mesoporous calcium carbonate vaterite crystals (CaCO3 vaterite) have recently attracted significant attention as inexpensive and biocompatible carriers for the encapsulation and controlled release of both drugs and nanoparticles. This work aimed to develop an approach to load AgNPs into CaCO3 vaterite without affecting their properties. We focused on improving the colloidal stability of AgNPs by using different capping agents, and understanding the mechanism behind AgNPs loading and release from CaCO3 crystals. Various methods were applied to study the AgNPs and CaCO3 crystals loaded with AgNPs (CaCO3/AgNPs hybrids), such as scanning and transmission electron microscopy, X-ray diffraction, infrared and mass spectrometry. The results demonstrated that polyvinylpyrrolidone and positively charged diethylaminoethyl-dextran can effectively keep the colloidal stability of AgNPs during co-precipitation with CaCO3 crystals. CaCO3/AgNPs hybrids composed of up to 4 % weight content of nanoparticles were produced, with the loading mechanism being well-described by the Langmuir adsorption model. In vitro release studies demonstrated a burst release of stable AgNPs at pH 5.0 and a sustained release at pH 7.5 and 9.0. The antibacterial studies showed that these hybrids are effective against Escherichia coli, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa, three important bacteria responsible for nosocomial infections. The developed approach opens a new way to stabilise, protect, store and release AgNPs in a controlled manner for their use as antimicrobial agents.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Calcium carbonate; Dextran; Immobilisation; Polyvinylpyrrolidone; Vaterite